High polymer material for reducing springback of tunnel shotcrete and preparation method of high polymer material
By using Elostone nanotubes to modify @cellulose, the problem of rebound loss of tunnel jet concrete is solved, and the effect of improving concrete adhesion ability and homogeneity is achieved, and the quality and safety of tunnel structure are improved.
Patent Information
- Application Number
- CN202411787644.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-14
AI Technical Summary
During the tunnel spray concrete process, some concrete failed to adhere to the rock wall surface, resulting in rebound loss, increasing the risk of material waste and tunnel structure quality and safety.
Elosite nanotube modified @cellulose is used as a polymer material. Through surface modification treatment and grafting reaction, the adhesion ability and homogeneity of concrete are improved and rebound loss is reduced.
It effectively reduces the rebound rate of tunnel jet concrete, improves the corrosion resistance and final strength of concrete, and improves the quality and safety of tunnel structure.
Smart Images

Figure BDA0005174483630000121 
Figure BDA0005174483630000131
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete additive preparation, in particular to a polymer material for reducing the rebound of tunnel shotcrete and a preparation method thereof. Background Art
[0002] After tunnel excavation, concrete needs to be sprayed on the cracked rock wall. After the concrete sprayed on the rock wall solidifies, it forms the initial support for the tunnel. The commonly used concrete spraying method is mainly wet spraying. The specific operation of wet spraying is as follows: first, the concrete is configured, and the pre-prepared concrete is input into the corresponding spraying equipment. The spraying equipment uses high-pressure air to transport the concrete to the nozzle. The nozzle sprays the concrete at a high spraying speed onto the cracked rock surface. After the concrete solidifies, it forms the initial support for the tunnel.
[0003] At present, the technical difficulties encountered by wet concrete spraying are as follows: during the spraying process of concrete, part of the concrete fails to adhere to the surface of the rock wall. During the spraying process of the concrete, part of the concrete is rebounded by the surface of the rock wall, which inevitably causes waste of concrete materials. The rebounded concrete also increases the difficulty of road cleaning, and may also have an adverse effect on the quality and safety of the tunnel structure. In the prior art, in order to reduce the rebound rate during concrete spraying, an appropriate amount of viscosity enhancer is usually added to the prepared concrete to improve the adhesion ability of the concrete toughening, thereby facilitating the prepared concrete to have a good adhesion strength with the rock wall surface and reduce the concrete rebound loss caused by particle collision and rebound.
[0004] In actual tunnel construction, the concrete viscosity enhancer is mainly silica fume. By adding an appropriate amount of silica fume, the overall adhesion of concrete is improved, thereby reducing the rebound loss of concrete during the wet spraying process. However, the addition of silica fume will inevitably increase the early shrinkage of concrete, leading to an increase in the risk of cracking and water seepage of the concrete layer that plays an initial supporting role on the surface of the broken rock wall, which is not conducive to improving the quality and safety of the tunnel structure. For this reason, there is an urgent need for a polymer material that reduces the rebound of tunnel shotcrete. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a polymer material for reducing the rebound of tunnel shotcrete and a preparation method thereof.
[0006] The polymer material for reducing the rebound of tunnel shotcrete provided by the present invention is realized by the following technical solutions:
[0007] A polymer material for reducing the rebound of tunnel shotcrete is cellulose modified with halloysite nanotubes. The cellulose modified with halloysite nanotubes is made of the following raw materials: cellulose, an alkaline catalyst, a surface modifier, halloysite nanotubes, and a solvent. The cellulose is prepared from cellulose wet pulp, and the cellulose in the cellulose wet pulp is at least one of cotton cellulose, potato cellulose, sugarcane cellulose, and straw cellulose. The alkaline catalyst is at least one of ammonia water, sodium hydroxide, potassium hydroxide, and sodium bicarbonate. The surface modifier includes an aqueous polyurethane emulsion, and the polyurethane latex in the aqueous polyurethane emulsion is terminated with hydroxyethyl acrylate. The halloysite nanotubes are surface treated with amino acids or aminosilanes.
[0008] Preferably, the surface modifier is composed of an aqueous polyurethane emulsion, a suspending agent, a dispersant, and an inhibitor, the mass of the suspending agent accounts for 0.04-0.12wt% of the total mass of the surface modifier; the suspending agent is a plant gum, and the plant gum is at least one of xanthan gum, locust bean gum, and konjac gum; the dispersant is deionized water or a mixed dispersant formed by deionized water and a strong polar organic solvent, and the strong polar organic solvent is at least one of acetone, N,N-dimethylformamide, toluene, and xylene; the polyurethane latex in the aqueous polyurethane emulsion accounts for 0.1-5.0wt% of the total mass of the surface modifier; the inhibitor is a quinone inhibitor, and the quinone inhibitor accounts for 0.05-0.2wt% of the total mass of the surface modifier.
[0009] Preferably, the average particle size of the polyurethane latex in the aqueous polyurethane emulsion is 100-250 nm; and the conversion temperature Tg of the polyurethane latex in the aqueous polyurethane emulsion is lower than -30°C.
[0010] Preferably, the aqueous polyurethane emulsion is made of the following raw materials: diisocyanate, polyol, chain extender, end-capping agent, deionized water, acetone, leveling agent, antioxidant, polymerization inhibitor, catalyst; the polymerization inhibitor is a quinone polymerization inhibitor, and the quinone polymerization inhibitor accounts for 0.15-0.50wt% of the total mass of the aqueous polyurethane emulsion; the chain extender is a small molecule diol and dimethylol propionic acid; the polyol is at least one of polyether polyol, polyester polyol, and polycarbonate polyol; the diisocyanate is a quinone polymerization inhibitor, and the quinone polymerization inhibitor accounts for 0.15-0.50wt% of the total mass of the aqueous polyurethane emulsion; the chain extender is a small molecule diol and dimethylol propionic acid; the polyol is at least one of polyether polyol, polyester polyol, and polycarbonate polyol; The isocyanate is an aromatic diisocyanate or a mixture of an aromatic diisocyanate and an aliphatic isocyanate; the end-capping agent is hydroxyethyl acrylate; the ratio of the molar amount of -NCO in the diisocyanate to the total molar amount of -OH in the polyol and the chain extender is (1.05-1.20):1; the molar amount of the hydroxyethyl acrylate is 1.04-1.15 times the difference between the molar amount of -NCO in the diisocyanate and the total molar amount of -OH in the polyol and the chain extender.
[0011] Preferably, the ratio of the molar amount of -NCO in the diisocyanate to the total molar amount of -OH in the polyol and the chain extender is (1.08-1.12):1; the molar amount of the hydroxyethyl acrylate is 1.06-1.10 times the difference between the molar amount of -NCO in the diisocyanate and the total molar amount of -OH in the polyol and the chain extender.
[0012] Preferably, the polyol is composed of a polycarbonate diol with a molecular weight of 1000-2000 and a polyether diol with a molecular weight of 1000-3000, and the molar ratio of the polycarbonate diol to the polyether diol is (0.8-1.5):1; the polycarbonate diol is polycaprolactone hexamethylene carbonate diol; and the polyether diol is polytetrahydrofuran diol PTMEG or branched polytetrahydrofuran diol.
[0013] Preferably, the preparation method of the aqueous polyurethane emulsion is as follows: accurately measured diisocyanate, polyol, antioxidant and catalyst are mixed uniformly, heated to 75-95°C for reaction for 1-2h, then a chain extender is added, the reaction is carried out at 75-95°C for 0.5-2h, the temperature is adjusted to 65-75°C, an inhibitor is added, and after mixing uniformly, a capping agent is added, the reaction is carried out at 65-75°C for 0.5-1.0h, a pH adjuster is added, stirred and mixed for neutralization for 1-5min, and finally deionized water, acetone and leveling agent are added, and acetone is removed by distillation after high-speed shear emulsification to obtain a finished aqueous polyurethane emulsion, which is stored at low temperature away from light for standby use.
[0014] The preparation method of the aqueous polyurethane emulsion provided by the present invention is relatively simple, convenient for batch production and manufacturing, reduces the use cost of the aqueous polyurethane emulsion, and is beneficial to optimizing the overall construction cost of concrete.
[0015] Preferably, the amino acid used for surface treatment of halloysite nanotubes is at least one of isoleucine, D-alanine, D-methionine, valine, leucine, and isoleucine; the aminosilane used for surface treatment of halloysite nanotubes is at least one of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, and γ-aminopropylmethyldiethoxysilane.
[0016] By adopting the above technical scheme to introduce active amino groups on the surface of halloysite nanotubes, the overall hydrophilicity of the halloysite nanotubes can be improved, and it is also convenient for the subsequent grafting of the halloysite nanotubes to cellulose to form halloysite-modified @cellulose ether. The prepared halloysite-modified @cellulose ether can not only improve the overall adhesion ability of concrete, reduce the rebound loss of concrete during the wet spraying process, but also delay the generation of hydration heat peak, improve the homogeneity of concrete, effectively inhibit early plastic cracks and shrinkage cracks, but also improve the corrosion resistance and ultimate strength of concrete, which is beneficial to the improvement of the quality and safety of tunnel structures.
[0017] The present invention provides a method for preparing a polymer material for reducing the rebound of tunnel shotcrete, which is achieved through the following technical solutions:
[0018] A method for preparing a polymer material for reducing the rebound of tunnel shotcrete comprises the following steps:
[0019] Step 1, surface modification of halloysite nanotubes;
[0020] The preparation of the surface modifier and the alkali treatment of the cellulose are performed simultaneously;
[0021] Step 2, after the surface-modified halloysite nanotubes, the surface modifier and the solvent are mixed, the temperature is raised to 70-75° C. under nitrogen protection for reaction for 0.5-1.0 h, and after cooling to room temperature, the reduced pressure filtration is performed, and the obtained filter material is rinsed with deionized water at least three times, and the filter material after the deionized water rinse is mixed with acetone to form a suspension, and the mass ratio of the acetone to the filter material is (2-4):1;
[0022] Step three, add an alkaline catalyst to the suspension, adjust the pH value of the system to ≥10, add cellulose treated with alkali reduction, adjust the temperature to 25-30°C and 0.8-1.6MPa, react at 30-60rpm for 4-8h, and filter under reduced pressure after the reaction is completed. Rinse the obtained filter material with deionized water to neutrality, and then vacuum dry it. The obtained solid is placed in a jet mill for crushing and screening to obtain the finished product of halloysite nanotube-modified cellulose.
[0023] The preparation method of the present invention is relatively simple, has low operating difficulty, and is easy to realize industrial batch production.
[0024] Preferably, in step one, the surface modification of the halloysite nanotubes is performed, and the specific operation is as follows: the halloysite nanotubes are subjected to ball milling dispersion treatment, and then placed at 160-240°C for heat treatment activation for 1-2h, the ball-milled + activated halloysite nanotubes are added to an amino acid aqueous solution or an aminosilane aqueous solution with a concentration of 0.01-0.10 mol / L, first stirred and mixed at a speed of 60-120 rpm for 5-15 minutes, and then ultrasonically dispersed for 15-60 minutes, filtered under reduced pressure, and the obtained solid was vacuum dried and then input into a planetary ball mill for high-speed ball milling dispersion treatment to obtain the finished halloysite nanotubes.
[0025] The active -NH 2 The functional group and the -NH-CO urethane bond in the polyurethane latex molecular chain in the aqueous polyurethane solution are reacted under acidic catalytic conditions to form the finished halloysite nanotube -NH 2R-NH-CO-NH-halloysite nanotubes are produced by nucleophilic reaction with polyurethane latex, wherein R in the obtained R-NH-CO-NH-halloysite nanotubes is terminated with hydroxyacrylate, that is, the double bond in R is produced by reacting with cellulose treated with alkali reduction under alkaline conditions, and R-NH-CO-NH-halloysite nanotubes are grafted onto the main chain of cellulose. The grafting of R-NH-CO-NH-halloysite nanotubes to the main chain can improve the early performance and ultimate strength of concrete, effectively inhibit early plastic cracks and shrinkage cracks, and is beneficial to the improvement of the quality and safety of tunnel structures. In addition, the porous structure of halloysite nanotubes can effectively store effective ions such as chloride ions and sulfate ions, thereby improving the corrosion resistance of concrete.
[0026] In summary, the present invention has the following advantages:
[0027] 1. The present invention can improve the adhesion of the whole concrete, reduce the rebound loss of concrete during the wet spraying process, delay the generation of hydration heat peak, improve the homogeneity of concrete, effectively inhibit early plastic cracks and shrinkage cracks, and help improve the quality and safety of tunnel structures.
[0028] 2. In the present invention, halloysite nanotubes are grafted onto cellulose to form halloysite-modified cellulose ether, which not only improves the overall adhesion of concrete, reduces the rebound loss of concrete during the wet spraying process, effectively inhibits early plastic cracks and shrinkage cracks, but also improves the corrosion resistance and ultimate strength of concrete, which is beneficial to the improvement of the quality and safety of tunnel structures.
[0029] 3. The preparation method of the present invention is relatively simple, has low operating difficulty, and is easy to realize industrial batch production. DETAILED DESCRIPTION
[0030] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples and comparative examples.
[0031] Example
[0032] A polymer material for reducing the rebound of tunnel shotcrete is halloysite nanotube-modified cellulose. The halloysite nanotube-modified cellulose is made of the following raw materials: cellulose, an alkaline catalyst, a surface modifier, halloysite nanotubes, and a solvent.
[0033] The cellulose is prepared from cellulose wet pulp, and the cellulose in the cellulose wet pulp is at least one of cotton cellulose, potato cellulose, sugarcane cellulose and straw cellulose.
[0034] The alkaline catalyst is at least one of ammonia water, sodium hydroxide, potassium hydroxide and sodium bicarbonate.
[0035] The surface modifier comprises waterborne polyurethane emulsion, the polyurethane latex in the waterborne polyurethane emulsion is terminated with hydroxyethyl acrylate, the average particle size of the polyurethane latex in the waterborne polyurethane emulsion is 100-250nm, and the conversion temperature Tg of the polyurethane latex is lower than -30℃.
[0036] Specifically, the surface modifier is composed of an aqueous polyurethane emulsion, a suspending agent, a dispersant, and an inhibitor. The mass of the suspending agent accounts for 0.04-0.12wt% of the total mass of the surface modifier. The suspending agent is a plant gum, and the plant gum is at least one of xanthan gum, locust bean gum, and konjac gum. The dispersant is deionized water or a mixed dispersant formed by deionized water and a strong polar organic solvent. The strong polar organic solvent is at least one of acetone, N,N-dimethylformamide, toluene, and xylene. The polyurethane latex in the aqueous polyurethane emulsion accounts for 0.1-5.0wt% of the total mass of the surface modifier. The inhibitor is a quinone inhibitor, and the quinone inhibitor accounts for 0.05-0.2wt% of the total mass of the surface modifier.
[0037] Waterborne polyurethane emulsion is made of the following raw materials: diisocyanate, polyol, chain extender, end-capping agent, deionized water, acetone, leveling agent, antioxidant, inhibitor and catalyst.
[0038] The polymerization inhibitor is a quinone polymerization inhibitor, which accounts for 0.15-0.50wt% of the total weight of the waterborne polyurethane emulsion.
[0039] The chain extender is a small molecule diol and dimethylol propionic acid, and the small molecule diol is butanediol or hexanediol.
[0040] The polyol is at least one of polyether polyol, polyester polyol and polycarbonate polyol. Preferably, the polyol is a polycarbonate diol with a molecular weight of 1000-2000 and a polyether diol with a molecular weight of 1000-3000. Specifically, the molar ratio of the polycarbonate diol to the polyether diol is (0.8-1.5):1, the polycarbonate diol is polycaprolactone hexamethylene carbonate diol, and the polyether diol is polytetrahydrofuran diol PTMEG or branched polytetrahydrofuran diol.
[0041] The diisocyanate is an aromatic diisocyanate or a mixture of an aromatic diisocyanate and an aliphatic isocyanate.
[0042] The end-capping agent is hydroxyethyl acrylate, specifically hydroxyethyl acrylate and / or hydroxyethyl methacrylate.
[0043] The ratio of the molar amount of -NCO in the diisocyanate to the total molar amount of -OH in the polyol and the chain extender is (1.05-1.20):1.
[0044] Preferably, the ratio of the molar amount of -NCO in the diisocyanate to the total molar amount of -OH in the polyol and the chain extender is (1.08-1.12):1.
[0045] The molar amount of hydroxyethyl acrylate is 1.04-1.15 times the difference between the molar amount of -NCO in the diisocyanate and the total molar amount of -OH in the polyol and the chain extender.
[0046] Preferably, the molar amount of hydroxyethyl acrylate is 1.06-1.10 times the difference between the molar amount of -NCO in the diisocyanate and the total molar amount of -OH in the polyol and the chain extender.
[0047] The preparation method of the waterborne polyurethane emulsion is as follows: accurately measured diisocyanate, polyol, antioxidant and catalyst are mixed evenly, heated to 75-95°C for reaction for 1-2h, then a chain extender is added, the reaction is carried out at 75-95°C for 0.5-2h, the temperature is adjusted to 65-75°C, an inhibitor is added, and after mixing evenly, a capping agent is added, the reaction is carried out at 65-75°C for 0.5-1.0h, a pH adjuster is added, stirred and mixed for neutralization for 1-5min, and finally deionized water, acetone and a leveling agent are added, and the acetone is removed by distillation after high-speed shear emulsification to obtain a finished waterborne polyurethane emulsion, which is stored at low temperature away from light for future use.
[0048] The halloysite nanotubes were treated with surface amino acids or aminosilanes.
[0049] The amino acid used for surface treatment of halloysite nanotubes is at least one of isoleucine, D-alanine, D-methionine, valine, leucine and isoleucine.
[0050] The aminosilane used for surface treatment of halloysite nanotubes is at least one of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane and γ-aminopropylmethyldiethoxysilane.
[0051] A method for preparing a polymer material for reducing the rebound of tunnel shotcrete comprises the following steps:
[0052] Step 1, surface modification of the halloysite nanotubes, specifically, the following operations: ball-milling and dispersing the halloysite nanotubes, then heat-treating and activating them at 160-240° C. for 1-2 hours, adding the ball-milled and activated halloysite nanotubes to an aqueous amino acid solution or an aminosilane solution with a concentration of 0.01-0.10 mol / L, stirring and mixing at a speed of 60-120 rpm for 5-15 minutes, then performing ultrasonic dispersion treatment for 15-60 minutes, filtering under reduced pressure, and vacuum drying the obtained solids and then inputting them into a planetary ball mill for high-speed ball milling and dispersion treatment to obtain finished halloysite nanotubes;
[0053] At the same time, the surface modifier is prepared, and the specific operation is as follows: firstly, an aqueous polyurethane emulsion is prepared, and then the accurately measured aqueous polyurethane emulsion, suspending agent, dispersing agent and polymerization inhibitor are mixed uniformly according to the proportion;
[0054] and alkali treatment of cellulose; placing the cellulose wet pulp in a 1-5wt% sodium hydroxide aqueous solution for alkali reduction treatment for 15-60 minutes, filtering the obtained filter material and washing it with deionized water until it is neutral to obtain the finished cellulose raw material;
[0055] Step 2, after the surface-modified halloysite nanotubes, the surface modifier and the solvent are mixed, the temperature is raised to 70-75° C. under nitrogen protection for reaction for 0.5-1.0 h, and after cooling to room temperature, the reduced pressure filtration is performed, and the obtained filter material is rinsed with deionized water at least three times, and the filter material after the deionized water rinse is mixed with acetone to form a suspension, and the mass ratio of the acetone to the filter material is (2-4):1;
[0056] Step three, add an alkaline catalyst to the suspension, adjust the pH value of the system to ≥10, add cellulose treated with alkali reduction, adjust the temperature to 25-30°C and 0.8-1.6MPa, react at 30-60rpm for 4-8h, and filter under reduced pressure after the reaction is completed. Rinse the obtained filter material with deionized water to neutrality, and then vacuum dry it. The obtained solid is placed in a jet mill for crushing and screening to obtain the finished product of halloysite nanotube-modified cellulose.
[0057] Example 1: A method for preparing a polymer material for reducing the rebound of tunnel shotcrete is as follows:
[0058] Step 1, the surface of the halloysite nanotubes is modified, and the specific operation is as follows: the halloysite nanotubes (purchased from Suzhou Kaifa New Materials Technology Co., Ltd.) are placed in a planetary ball mill, and zirconium oxide is used as grinding beads for wet ball milling dispersion treatment. 1g of the halloysite nanotubes is mixed with 5g of ethanol aqueous solution and ball milled at 80rpm for 30min. The obtained ball-milled halloysite nanotubes are filtered and vacuum dried. The obtained halloysite nanotubes are heat-treated and activated at 220°C for 1h, and then 1g of the ball-milled + activated halloysite nanotubes are added to 50mL of a 0.01mol / L D-methionine aqueous solution, first stirred and mixed at a speed of 120rpm for 5min, and then ultrasonically dispersed for 30min, the ultrasonic dispersion parameter is 40kHz / 450W, and finally the liquid material is filtered under reduced pressure, and the obtained solid is vacuum dried and input into a planetary ball mill for high-speed dry ball milling dispersion treatment, and ball milled at 800rpm for 2h to obtain the finished halloysite nanotubes;
[0059] At the same time, the surface modifier is prepared, and the specific operation is as follows:
[0060] First, prepare an aqueous polyurethane emulsion: 255.3 g of MDI, 560 g of polycarbonate 3-methyl 1,5 pentanediol-1,6-hexanediol ester diol C-2020, 5 g of antioxidant 1010, and 0.5 g of catalyst-dibutyltin dilaurate are mixed and stirred at 120 rpm for 5 min, heated to 80 ° C and reacted for 2 h, then 29.5 g of 2,2-dihydroxymethylpropionic acid and 52 g of 1,6-hexanediol are added, reacted at 85 ° C for 85 min, and the temperature is adjusted to 75 ° C, and then added 3g of methylhydroquinone was mixed and stirred at 120rpm for 8min, then 13.9g of end-capping agent - hydroxyethyl acrylate was added, and the mixture was reacted at 75°C for 1.0h. Dimethylethanolamine was added to adjust the pH value of the system to neutral, and then the mixture was stirred and mixed for 5min. Finally, 1500g of deionized water, 215g of acetone, and 8g of leveling agent RM2020 were added. After high-speed shear emulsification, the acetone was removed by distillation to obtain the finished waterborne polyurethane emulsion, which was stored at low temperature away from light for future use;
[0061] According to the ratio, 50 g of accurately measured water-based polyurethane emulsion, 0.7 g of suspending agent-xanthan gum, 450 g of deionized water, 198.6 g of acetone, and 0.7 g of inhibitor methyl hydroquinone are mixed evenly to obtain a surface modifier;
[0062] Alkali treatment of cellulose: 50 g of cellulose wet pulp (cotton fiber, water content 60 wt%) was placed in 250 mL of 5 wt % sodium hydroxide aqueous solution, and subjected to alkali reduction treatment at 200 rpm for 60 min. The filter material was filtered and washed with deionized water until neutral, and the finished cellulose raw material was obtained;
[0063] Step 2, 1g of surface-modified halloysite nanotubes, 10g of surface modifier and 19g of acetone / DMF solvent (mixed with 10g acetone + 9g DMF) were mixed and stirred at 120rpm for 5min, heated to 75°C under nitrogen protection for 1.0h, cooled to room temperature and filtered under reduced pressure, the obtained filter material was rinsed three times with deionized water, and 1 part by mass of the filter material was mixed with 4 parts by mass of acetone to form a suspension;
[0064] Step three, add a 10wt% KOH aqueous solution to the suspension, adjust the system pH to 12, add the finished cellulose raw material obtained by alkali reduction treatment in step one, adjust the temperature to 25°C and 1.0MPa, react at 45rpm for 8.0h, and filter under reduced pressure after the reaction is completed. Rinse the obtained filter material with deionized water to neutrality, and then vacuum dry it. The obtained solid is placed in a jet mill for crushing and sieving to obtain a finished cellulose product with an average particle size of 0.5-2μm.
[0065] The difference between Example 2 and Example 1 is that in step 1, 1 g of ball-milled and activated halloysite nanotubes is added to 50 mL of a 0.05 mol / L D-methionine aqueous solution, first stirred and mixed at 120 rpm for 5 min, and then ultrasonically dispersed for 30 min.
[0066] The difference between Example 3 and Example 1 is that in step 1, 1 g of ball-milled and activated halloysite nanotubes is added to 50 mL of a 0.10 mol / L D-methionine aqueous solution, first stirred and mixed at 120 rpm for 5 min, and then ultrasonically dispersed for 30 min.
[0067] The difference between Example 4 and Example 1 is that in step 1, 1 g of ball-milled + activated halloysite nanotubes is added to 50 mL of a 0.01 mol / L γ-aminopropyltriethoxysilane aqueous solution, first stirred and mixed at 120 rpm for 5 min, and then ultrasonically dispersed for 30 min.
[0068] The difference between Example 5 and Example 1 is that in step 1, 1 g of ball-milled and activated halloysite nanotubes is added to 50 mL of a 0.05 mol / L γ-aminopropyltriethoxysilane aqueous solution, first stirred and mixed at 120 rpm for 5 min, and then ultrasonically dispersed for 30 min.
[0069] The difference between Example 6 and Example 1 is that in step 1, 1 g of ball-milled + activated halloysite nanotubes is added to 50 mL of a 0.10 mol / L γ-aminopropyltriethoxysilane aqueous solution, first stirred and mixed at 120 rpm for 5 min, and then ultrasonically dispersed for 30 min.
[0070] The difference between Example 7 and Example 1 is that: in step 1, an aqueous polyurethane emulsion is prepared: 255.3 g of MDI, 336 g of polycarbonate 3-methyl 1,5 pentanediol-1,6-hexanediol ester diol C-2020, 224 g of polytetrahydrofuran diol PTMEG, 5 g of antioxidant 1010, and 0.5 g of catalyst-dibutyltin dilaurate are mixed and stirred at 120 rpm for 5 min, heated to 80 ° C and reacted for 2 h, then 29.5 g of 2,2-dihydroxymethylpropionic acid and 52 g of 1,6-hexanediol are added, and the reaction is carried out at 85 ° C for 85 min, and the temperature is adjusted to 100 ° C. At 75°C, add 3g of methylhydroquinone, stir at 120rpm for 8min, then add 14.1g of end-capping agent - hydroxyethyl acrylate, react at 75°C for 1.0h, add dimethylethanolamine to adjust the pH value of the system to neutral, stir and mix for 5min, finally add 1500g of deionized water, 215g of acetone, and 8g of leveling agent RM2020, emulsify at high speed, and distill to remove acetone to obtain the finished waterborne polyurethane emulsion, which should be stored at low temperature away from light for future use.
[0071] The difference between Example 8 and Example 1 is that: in step 1, an aqueous polyurethane emulsion is prepared: 255.3 g of MDI, 240 g of polycarbonate 3-methyl 1,5 pentanediol-1,6-hexanediol ester diol C-2020, 320 g of polytetrahydrofuran diol PTMEG, 5 g of antioxidant 1010, and 0.5 g of catalyst-dibutyltin dilaurate are mixed and stirred at 120 rpm for 5 min, heated to 80 ° C and reacted for 2 h, then 29.5 g of 2,2-dihydroxymethylpropionic acid and 52 g of 1,6-hexanediol are added, and the reaction is carried out at 85 ° C for 85 min, and the temperature is adjusted to 100 ° C. At 75°C, add 3g of methylhydroquinone, stir at 120rpm for 8min, then add 14.1g of end-capping agent - hydroxyethyl acrylate, react at 75°C for 1.0h, add dimethylethanolamine to adjust the pH value of the system to neutral, stir and mix for 5min, finally add 1500g of deionized water, 215g of acetone, and 8g of leveling agent RM2020, emulsify at high speed, and distill to remove acetone to obtain the finished waterborne polyurethane emulsion, which should be stored at low temperature away from light for future use.
[0072] The difference between Example 9 and Example 1 is that the preparation method of the surface modifier in step 1 is as follows: 5 g of accurately measured aqueous polyurethane emulsion, 0.7 g of suspending agent-xanthan gum, 1200 g of deionized water, 543.4 g of acetone, and 0.9 g of inhibitor methylhydroquinone are mixed uniformly according to the ratio to obtain the surface modifier.
[0073] The difference between Example 10 and Example 1 is that the preparation method of the surface modifier in step 1 is as follows: 5 g of accurately measured aqueous polyurethane emulsion, 0.3 g of suspending agent-xanthan gum, 200 g of deionized water, 144.3 g of acetone, and 0.4 g of inhibitor methylhydroquinone are mixed uniformly according to the ratio to obtain the surface modifier.
[0074] The difference between Example 11 and Example 1 is that the preparation method of the surface modifier in step 1 is as follows: 50 g of accurately measured aqueous polyurethane emulsion, 1 g of suspending agent-xanthan gum, 1000 g of deionized water, 697.5 g of acetone, and 1.5 g of inhibitor methylhydroquinone are mixed evenly according to the ratio to obtain the surface modifier.
[0075] The difference between Example 12 and Example 1 is that the preparation method of the surface modifier in step 1 is as follows: 50 g of accurately measured aqueous polyurethane emulsion, 0.3 g of suspending agent-xanthan gum, 200 g of deionized water, 99.3 g of acetone, and 0.4 g of inhibitor methylhydroquinone are mixed uniformly according to the ratio to obtain the surface modifier.
[0076] The difference between Comparative Example 1 and Example 1 is that: Step 1, the surface modification of the halloysite nanotubes is performed, and the specific operation is as follows: the halloysite nanotubes are placed in a planetary ball mill, and zirconium oxide is used as grinding beads for wet ball milling dispersion treatment. 1g of the halloysite nanotubes is mixed with 5g of ethanol aqueous solution and ball milled at 80rpm for 30min. The obtained ball-milled halloysite nanotubes are filtered and vacuum dried. The obtained halloysite nanotubes are heat-treated and activated at 220°C for 1h, and then the ball-milled + activated halloysite nanotubes are added to deionized water with a concentration of 50%, first stirred and mixed at a speed of 120rpm for 5min, and then ultrasonic dispersion is performed for 30min, and the ultrasonic dispersion parameters are 40kHz / 450W. Finally, the liquid material is filtered under reduced pressure, and the obtained solid is vacuum dried and input into a planetary ball mill for high-speed dry ball milling dispersion treatment, and ball milled at 800rpm for 2h to obtain the finished halloysite nanotubes.
[0077] The difference between Comparative Example 2 and Example 1 is that in step 1, 1 g of ball-milled + activated halloysite nanotubes is added to 50 mL of a 0.005 mol / L D-methionine aqueous solution, first stirred and mixed at 120 rpm for 5 min, and then ultrasonically dispersed for 30 min.
[0078] The difference between Comparative Example 3 and Example 1 is that in step 1, 1 g of ball-milled + activated halloysite nanotubes is added to 50 mL of a 0.15 mol / L D-methionine aqueous solution, first stirred and mixed at 120 rpm for 5 min, and then ultrasonically dispersed for 30 min.
[0079] The difference between Comparative Example 4 and Example 1 is that in step 1, 1 g of ball-milled + activated halloysite nanotubes is added to 50 mL of a 0.005 mol / L γ-aminopropyltriethoxysilane aqueous solution, first stirred and mixed at 120 rpm for 5 min, and then ultrasonically dispersed for 30 min.
[0080] The difference between Comparative Example 5 and Example 1 is that in step 1, 1 g of ball-milled + activated halloysite nanotubes is added to 50 mL of a 0.15 mol / L γ-aminopropyltriethoxysilane aqueous solution, first stirred and mixed at 120 rpm for 5 min, and then ultrasonically dispersed for 30 min.
[0081] The difference between Comparative Example 6 and Example 1 is that: in step 1, an aqueous polyurethane emulsion is prepared: 200 g of MDI, 560 g of polyadipate-3-methyl 1,5-pentanediol ester diol (Japan Kuraray P-2010), 5 g of antioxidant 1010, and 0.5 g of catalyst-dibutyltin dilaurate are mixed and stirred at 120 rpm for 5 min, heated to 80 ° C and reacted for 2 h, then 29.5 g of 2,2-dihydroxymethylpropionic acid and 52 g of 1,6-hexanediol are added, reacted at 80 ° C for 1 h, and 56 g of end-capping agent-MD I is added. I, capping reaction at 80 ° C for 1.0h, adding dimethylethanolamine to adjust the pH value of the system to neutral and stirring and mixing for 5min, finally adding 1500g of deionized water, 200g of acetone, and 8g of leveling agent RM-2020, high-speed shear emulsification and distillation to remove acetone, to obtain -NCO-capped water-based polyurethane emulsion, which is stored at low temperature away from light for future use.
[0082] The difference between Comparative Example 7 and Example 1 is that the preparation method of the surface modifier in step 1 is as follows: 5 g of accurately measured aqueous polyurethane emulsion, 4 g of suspending agent-xanthan gum, 2800 g of deionized water, 687.5 g of acetone, and 3.5 g of inhibitor methylhydroquinone are mixed uniformly according to the ratio to obtain the surface modifier.
[0083] The difference between Comparative Example 8 and Example 1 is that the preparation method of the surface modifier in step 1 is as follows: 50 g of accurately measured aqueous polyurethane emulsion, 0.25 g of suspending agent-xanthan gum, 150 g of deionized water, 49.45 g of acetone, and 0.3 g of inhibitor methylhydroquinone are mixed evenly according to the ratio to obtain the surface modifier.
[0084] Performance testing
[0085] Concrete sample preparation: The base hydraulic concrete is made of water, stone (5-10mm), C25 cement, and river sand (fineness modulus 3.4) in a mass ratio of 176:892:440:892. The above materials are stirred at a speed of 45r / min for 5min to be uniformly stirred, and the halloysite nanotube-modified @cellulose in Examples 1-12 and Comparative Examples 1-8 are added respectively, with a doping amount of 1.0wt%, to prepare the machine-made mortar experimental groups 1-12 and comparative experimental groups 1-8. Control group 1: The base hydraulic concrete is made of water, stone (5-10mm), cement, and river sand (fineness modulus 3.4) in a mass ratio of 176:892:440:892. The above materials are stirred at a speed of 45r / min for 5min to prepare the control machine-made mortar. Control group 1: The benchmark hydraulic concrete was prepared according to the mass ratio of water, stone (5-10 mm), cement and river sand (fineness modulus 3.4) of 176:892:440:892. The above materials were stirred at a speed of 45 r / min for 5 min, and cellulose ether (De Shengya low viscosity hydroxypropyl methylcellulose ether type 400) was added with a doping amount of 0.5 wt% to prepare a control machine-made mortar.
[0086] According to the "Standard for Test Methods of Mechanical Properties of Ordinary Concrete" (GB / T 50081) and the "Test Procedures for Highway Cement and Cement Concrete", the slump, compressive strength and resilience of the shotcrete made from the machine-made mortar test groups 1-12, the comparative test groups 1-8 and the control group were tested. The sulfate corrosion resistance of cement was determined according to 4. Immersion corrosion resistance test method K in GB / T 749-2008 Test Methods for Sulfate Corrosion Resistance of Cement.
[0087] Data analysis
[0088] Table 1: Test parameters of concrete samples prepared with different halloysite nanotubes modified @cellulose
[0089]
[0090]
[0091] It can be seen from Examples 1-12 and Control Groups 1-2 and Table 1 that the concrete prepared using the halloysite nanotube-modified cellulose provided in the present invention not only has a low rebound rate, but also has good corrosion resistance and ultimate compressive strength, which is beneficial to improving the quality and safety of the tunnel structure.
[0092] Combining Examples 1-6 and Comparative Examples 1-5 and Table 1, it can be seen that the comprehensive performance of the concrete prepared by the modified @cellulose of the halloysite nanotubes prepared by the halloysite nanotubes treated with the amino acid aqueous solution or aminosilane aqueous solution at a concentration of 0.01-0.10 mol / L is relatively good. However, the amount of the halloysite nanotubes grafted on the cellulose surface by the halloysite nanotubes treated with too low an amino acid aqueous solution or aminosilane aqueous solution is relatively small, resulting in relatively low corrosion resistance and ultimate compressive strength of the concrete prepared therefrom; while the amount of the halloysite nanotubes grafted on the cellulose surface by the halloysite nanotubes treated with too high an amino acid aqueous solution or aminosilane aqueous solution is relatively large, which will affect the water absorption and moisture retention of the cellulose ether, and is not conducive to improving the corrosion resistance and ultimate compressive strength of the concrete prepared therefrom.
[0093] From Example 1, Examples 7-8 and Comparative Example 6 and Table 1, it can be seen that the halloysite nanotubes grafted on the cellulose ether in the halloysite nanotube-modified @cellulose prepared by the aqueous polyurethane terminated with hydroxy acrylate have good connection stability and are not easily hydrolyzed to cause the halloysite nanotubes and the cellulose ether to break and separate, so that the cellulose ether and the halloysite nanotubes are effectively distributed inside the machine-made slurry, which can improve the rebound rate of the concrete prepared therefrom, and at the same time improve the corrosion resistance and ultimate compressive strength of the concrete.
[0094] Combining Example 1, Examples 9-12 and Comparative Examples 7-8 and Table 1, it can be seen that the content of polyurethane latex in the surface modifier has a close influence on the prepared halloysite nanotube-modified cellulose. When the content of polyurethane latex is low, the polyurethane latex particles grafted on the surface of the halloysite nanotube are relatively small, resulting in a small number of halloysite nanotubes grafted on the cellulose ether, resulting in low final corrosion resistance and final compressive strength of the concrete. When the content of polyurethane latex is high, the polyurethane latex particles grafted on the surface of the halloysite nanotube are relatively large, which is easy to block the pores of the halloysite nanotubes. Although the final compressive strength of the concrete is improved, its corrosion resistance is adversely affected.
[0095] It can be seen from Examples 1-12 and Comparative Examples 1-8 and Table 1 that the present invention can improve the adhesion of the entire concrete, reduce the rebound loss of concrete during the wet spraying process, and delay the generation of the hydration heat peak, thereby improving the homogeneity of the concrete, effectively inhibiting early plastic cracks and shrinkage cracks, and improving the corrosion resistance and ultimate compressive strength of the concrete, which is beneficial to improving the quality and safety of the tunnel structure and enhancing the market competitiveness of the finished concrete additive.
[0096] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.
Claims
1. A polymer material for reducing the rebound of tunnel shotcrete, characterized in that: The polymer material for reducing the rebound of tunnel shotcrete is halloysite nanotube-modified cellulose, and the halloysite nanotube-modified cellulose is made of the following raw materials: cellulose, alkaline catalyst, surface modifier, halloysite nanotube, and solvent; The cellulose is prepared from cellulose wet pulp, and the cellulose in the cellulose wet pulp is at least one of cotton cellulose, potato cellulose, sugarcane cellulose and straw cellulose; The alkaline catalyst is at least one of ammonia water, sodium hydroxide, potassium hydroxide and sodium bicarbonate; The surface modifier comprises an aqueous polyurethane emulsion, wherein the polyurethane latex in the aqueous polyurethane emulsion is terminated with hydroxyethyl acrylate; The halloysite nanotubes are surface treated with amino acid or aminosilane.
2. The polymer material for reducing the rebound of tunnel shotcrete according to claim 1, characterized in that: The surface modifier is composed of an aqueous polyurethane emulsion, a suspending agent, a dispersing agent, and an inhibitor, wherein the mass of the suspending agent accounts for 0.04-0.12wt% of the total mass of the surface modifier; the suspending agent is a plant gum, which is at least one of xanthan gum, locust bean gum, and konjac gum; the dispersing agent is deionized water or a mixed dispersing agent formed by deionized water and a strong polar organic solvent, and the strong polar organic solvent is at least one of acetone, N,N-dimethylformamide, toluene, and xylene; the polyurethane latex in the aqueous polyurethane emulsion accounts for 0.1-5.0wt% of the total mass of the surface modifier; the inhibitor is a quinone inhibitor, which accounts for 0.05-0.2wt% of the total mass of the surface modifier.
3. The polymer material for reducing the rebound of tunnel shotcrete according to claim 2, characterized in that: The average particle size of the polyurethane latex in the aqueous polyurethane emulsion is 100-250nm; the conversion temperature Tg of the polyurethane latex in the aqueous polyurethane emulsion is lower than -30°C.
4. The polymer material for reducing the rebound of tunnel shotcrete according to claim 2, characterized in that: The aqueous polyurethane emulsion is made of the following raw materials: diisocyanate, polyol, chain extender, end-capping agent, deionized water, acetone, leveling agent, antioxidant, polymerization inhibitor, and catalyst; the polymerization inhibitor is a quinone polymerization inhibitor, and the quinone polymerization inhibitor accounts for 0.15-0.50wt% of the total mass of the aqueous polyurethane emulsion; the chain extender is a small molecule diol and dimethylol propionic acid; the polyol is at least one of polyether polyol, polyester polyol, and polycarbonate polyol; the diisocyanate The ester is an aromatic diisocyanate or a mixture of an aromatic diisocyanate and an aliphatic isocyanate; the end-capping agent is hydroxyethyl acrylate; the ratio of the molar amount of -NCO in the diisocyanate to the total molar amount of -OH in the polyol and the chain extender is (1.05-1.20):1; the molar amount of the hydroxyethyl acrylate is 1.04-1.15 times the difference between the molar amount of -NCO in the diisocyanate and the total molar amount of -OH in the polyol and the chain extender.
5. The polymer material for reducing the rebound of tunnel shotcrete according to claim 4, characterized in that: The ratio of the molar amount of -NCO in the diisocyanate to the total molar amount of -OH in the polyol and the chain extender is (1.08-1.12):1; the molar amount of the hydroxyethyl acrylate is 1.06-1.10 times the difference between the molar amount of -NCO in the diisocyanate and the total molar amount of -OH in the polyol and the chain extender.
6. The polymer material for reducing the rebound of tunnel shotcrete according to claim 4, characterized in that: The polyol is composed of a polycarbonate diol with a molecular weight of 1000-2000 and a polyether diol with a molecular weight of 1000-3000, and the molar ratio of the polycarbonate diol to the polyether diol is (0.8-1.5):1; the polycarbonate diol is polycaprolactone hexamethylene carbonate diol; and the polyether diol is polytetrahydrofuran diol PTMEG or branched polytetrahydrofuran diol.
7. The polymer material for reducing the rebound of tunnel shotcrete according to claim 4, characterized in that: The preparation method of the waterborne polyurethane emulsion is as follows: accurately measured diisocyanate, polyol, antioxidant and catalyst are mixed evenly, heated to 75-95° C. for reaction for 1-2 hours, then a chain extender is added, reacted at 75-95° C. for 0.5-2 hours, the temperature is adjusted to 65-75° C., a polymerization inhibitor is added, and after mixing evenly, a capping agent is added, reacted at 65-75° C. for 0.5-1.0 hours, a pH regulator is added, stirred and mixed for neutralization for 1-5 minutes, and finally deionized water, acetone and a leveling agent are added, and acetone is removed by distillation after high-speed shear emulsification to obtain a finished waterborne polyurethane emulsion, which is stored at low temperature away from light for future use.
8. The polymer material for reducing the rebound of tunnel shotcrete according to claim 1, characterized in that: The amino acid used for surface amino acid treatment is at least one of isoleucine, D-alanine, D-methionine, valine, leucine, and isoleucine; the aminosilane used for aminosilane treatment is at least one of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, and γ-aminopropylmethyldiethoxysilane.
9. A method for preparing a polymer material for reducing the rebound of tunnel shotcrete according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1, surface modification of halloysite nanotubes; The preparation of the surface modifier and the alkali treatment of the cellulose are performed simultaneously; Step 2, after the surface-modified halloysite nanotubes, the surface modifier and the solvent are mixed, the temperature is raised to 70-75° C. under nitrogen protection for reaction for 0.5-1.0 h, and after cooling to room temperature, the reduced pressure filtration is performed, and the obtained filter material is rinsed with deionized water at least three times, and the filter material after the deionized water rinse is mixed with acetone to form a suspension, and the mass ratio of the acetone to the filter material is (2-4):1; Step three, add an alkaline catalyst to the suspension, adjust the pH value of the system to ≥10, add cellulose treated with alkali reduction, adjust the temperature to 25-30°C and 0.8-1.6MPa, react at 30-60rpm for 4-8h, and filter under reduced pressure after the reaction is completed. Rinse the obtained filter material with deionized water to neutrality, and then vacuum dry it. The obtained solid is placed in a jet mill for crushing and screening to obtain the finished product of halloysite nanotube-modified cellulose.
10. The method for preparing a polymer material for reducing the rebound of tunnel shotcrete according to claim 9, characterized in that: In the step 1, the surface of the halloysite nanotubes is modified. The specific operation is as follows: the halloysite nanotubes are subjected to ball milling dispersion treatment, and then placed at 160-240° C. for heat treatment activation for 1-2 hours, the ball milled and activated halloysite nanotubes are added to an amino acid aqueous solution or an aminosilane aqueous solution with a concentration of 0.01-0.10 mol / L, first stirred and mixed at a speed of 60-120 rpm for 5-15 minutes, and then ultrasonically dispersed for 15-60 minutes, filtered under reduced pressure, and the obtained solids are vacuum dried and then input into a planetary ball mill for high-speed ball milling dispersion treatment to obtain finished halloysite nanotubes.